Postpanoptism: the new technologies of surveillance in the control societies - Recio Sastre, Alejandro (Resonancias. Revista de Filosofía, 2019)
The new technologies are systematically applied in the development of social control techniques, they are bringing obsolescence on the panoptic surveillance, there upon we could talk only about postpanoptism. The postpanoptism raises in the control societies overcoming the disciplinary societies context. Today the postpanoptism operates in the exceptionality moments like exclusion tool apart out the constituted legality. Also, the surveillance works in the economy space domain above flows of consumers, beyond disciplinary techniques that act in productive environment. The expose of the individuals’ bodies, desires and habits introduces ethic-political problematic about postpanoptics mechanisms.